2019
DOI: 10.1515/ijamh-2018-0158
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between spiritual health and health-promoting lifestyle among students

Abstract: Background One of the components of a healthy life is attending to spiritual needs, which can reduce harmful behaviors. The aim of the present study was to evaluate the relationship between spiritual health (SH) and health-promoting lifestyle (HPL) among students of Guilan University of Medical Sciences. Materials and methods The present cross-sectional study was conducted on 360 nursing and midwifery students at Guilan University of Medical Sciences. The data were collected using a self-administered socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Social support had a direct significant correlation with the HPB; in addition, social support, age, educational attainment, marital status, job, and income sufficiency were the predictors of the HPB. The mean total score of HPB was 2.72, which was consistent with a study on women at reproductive age [19], lower than a study on university students in Gilan, Iran [31], and higher than a similar study in Indonesia [32]. These results may be affected by Iranian culture, social environment, and participants' characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…Social support had a direct significant correlation with the HPB; in addition, social support, age, educational attainment, marital status, job, and income sufficiency were the predictors of the HPB. The mean total score of HPB was 2.72, which was consistent with a study on women at reproductive age [19], lower than a study on university students in Gilan, Iran [31], and higher than a similar study in Indonesia [32]. These results may be affected by Iranian culture, social environment, and participants' characteristics.…”
Section: Discussionsupporting
confidence: 83%
“…One component of a healthy life is attending to spiritual needs, which might reduce harmful behaviors. A recent study in Iran demonstrated that spiritual health had a positive relationship with the adoption of health-promoting behaviors ( Rafat et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the discussion of health, especially mental health, the type of thinking and beliefs of the individual have always been discussed. Because of the better and more intellectual the level of thinking, the healthier the person’s lifestyle and the greater the person’s mental health ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the components of a healthy life is attending to mental health and healthy thinking, which can reduce harmful behaviors ( 7 , 8 ), thus the connection between thinking and mental health is very important ( 9 ). As part of a project titled Positive Thinking and Healthy Living, academics were requested to examine the issue of “thinking” and focus the themes of their papers on thinking and its relationship to health in 2019 ( 10 ).…”
Section: Introductionmentioning
confidence: 99%